2020
DOI: 10.1080/23311908.2020.1853010
|View full text |Cite
|
Sign up to set email alerts
|

Afrikaans adaptation of the children’s hope scale: Validation and measurement invariance

Abstract: The overarching aim of this study was to validate the Afrikaans version of Snyder's (1997) Children's Hope Scale in a sample of children from Cape Town, South Africa. Within this process, the study aimed to test the measurement invariance across the English and Afrikaans language versions. The study used a crosssectional survey design, with a two-stage stratified random sample of 1022 children between the ages of 11-to 12-years-old. We selected the participants from 15 schools located in low and middle socio-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…In South Africa, Savahl and colleagues tested the suitability of Western developed measures of hedonic wellbeing (the Personal Wellbeing Index: Cummings & Lau, 2005) and eudaimonic wellbeing (i.e., the Children's Hope Scale: Snyder et al, 1997) with an adolescent sample. Confirmatory factor analysis found that both measures fit the data well (Savahl et al, 2017(Savahl et al, , 2020 and factorial invariance testing across higher and lower socioeconomic status groups found that the hedonic measure had scalar equivalence across groups (Savahl et al, 2017). Researchers working in Ghana (Wilson Fadiji et al, 2019) also found that Western developed measures of hedonia (the Satisfaction with Life Scale: Diener et al, 1985) and eudaimonia (the Meaning in Life Questionnaire: Steger et al, 2006) were a good fit to data gathered with their adult sample.…”
Section: A Social Evolutionary Conceptualization Of Eudaimonia and Hedoniamentioning
confidence: 87%
“…In South Africa, Savahl and colleagues tested the suitability of Western developed measures of hedonic wellbeing (the Personal Wellbeing Index: Cummings & Lau, 2005) and eudaimonic wellbeing (i.e., the Children's Hope Scale: Snyder et al, 1997) with an adolescent sample. Confirmatory factor analysis found that both measures fit the data well (Savahl et al, 2017(Savahl et al, , 2020 and factorial invariance testing across higher and lower socioeconomic status groups found that the hedonic measure had scalar equivalence across groups (Savahl et al, 2017). Researchers working in Ghana (Wilson Fadiji et al, 2019) also found that Western developed measures of hedonia (the Satisfaction with Life Scale: Diener et al, 1985) and eudaimonia (the Meaning in Life Questionnaire: Steger et al, 2006) were a good fit to data gathered with their adult sample.…”
Section: A Social Evolutionary Conceptualization Of Eudaimonia and Hedoniamentioning
confidence: 87%
“…In children, the hope theory has been introduced on the concept that “goal-directed hopeful thinking” is a requisite for development and survival and is related to experiencing positive emotions [ 39 - 41 ]. Hope within students (≤16 years of age) will also be assessed longitudinally by age-appropriate hope scales at week 0, week 8, week 10, month 6, and month 12.…”
Section: Methodsmentioning
confidence: 99%
“…(Snyder et al, 2007;Valle, et al, 2004). The Hope Scale has been broadly used with acceptable scale reliability in populations outside of the US, such as French adults (Gana et al, 2013), Serbian adolescents (Jovanović, 2013), Japanese undergraduates (Kato & Snyder, 2005), Chinese youths in both low and high income households (Lei, et al, 2019), and South African children (Savahl et al, 2020).…”
Section: Hope Theorymentioning
confidence: 99%